PENGARUH BAHAN AJAR HANDOUT DAN BUKU TEKS TERHADAP MOTIVASI BELAJAR DI SMP NEGERI 2 BAROMBONG - Aisyah, Nur; Usman, syahruddin; Syamsuddin (Istiqra: jurnal hasil penelitian, 2022)
This research aims to explain the effect of using handout teaching materials on the learning motivation of students at SMP Negeri 2 Barombong. This research has a quantitative approach. Meanwhile, the sample size for this research was 64 people, using a purposive sampling technique. The results of this research show that the use of handout teaching materials in Islamic Religious Education learning is in the high category. Meanwhile, the use of Islamic Religious Education teaching books is in the medium category. Then, students’ learning motivation in learning Islamic Religious Education shows that students’ learning motivation increases significantly. Meanwhile, students’ learning motivation in the control class was included in the low category, while the posttest showed that students’ motivation had increased. Then the difference in the influence of the use of handouts and textbooks on students’ learning motivation in Islamic Religious Education learning shows a correlation